Pembelajaran Pembelajaran PPKn Yang Progresif: Meninjau Penggunaan Media Digital Dan Pengembangan Kurikulum Merdeka Di SMA Negeri 14 Medan - Lisa Caroline Pakpahan; Sinaga, Andre Dwi Putra; Thereza Dwi Ningrum Siburian; Putri Lopiga Br Tarigan; Daniel R. Sihite; Iren Br Bangun; Fazli Rachman; Liber Siagian (Universitas Sains dan Teknologi Komputer, 2024)
Pancasila and Citizenship Education (PPKn) is a crucial subject that plays a pivotal role in shaping the character and fostering nationalism among students, particularly at the Senior High School (SMA) level. However, the practical implementation of PPKn often encounters various challenges. This research aims to observe and analyze the issues within the Pancasila and Citizenship Education (PPKn) learning process at Senior High School 14 Medan. The study employs a case study methodology, involving interviews with teachers and students, as well as observations and surveys. The findings indicate that teachers at the school have adapted to the use of digital media for teaching, such as projectors and smartphones. However, they still face challenges in implementing the independent curriculum (integrated curriculum). The study also reveals that teachers require further training in effectively and efficiently utilizing digital media, as well as incorporating icebreakers to create a more conducive atmosphere for students. Furthermore, the research unveils that the independent curriculum does not pose significant challenges for teachers who have previously experienced implementing self-directed learning concepts. Nevertheless, there is still room for improvement in enhancing student engagement and providing better guidance from teachers during the learning process. Based on these findings, the research recommends several improvements to the current education system, including providing training for teachers in utilizing digital media, enhancing the independent curriculum, and increasing student involvement in the learning process. These recommendations aim to address the identified challenges and create a more effective and engaging PPKn learning environment in Senior High School 14 Medan.